SAT0387 Ultrasonographic and Clinical Assessment of Peripheral Enthesitis in Italian Patients with Psoriatic Arthritis, Psoriasis and Fibromyalgia –The ULISSE Study. (10th June 2014) - Salvarani, C.; Grassi, W.; Spadaro, A.; Grembiale, R.D.; Govoni, M.; Ramonda, R.; Marchesoni, A.; Scarpa, R.; De Vita, S.; Saragaglia, V.; Merolla, R.; di Luzio Paparatti, U.; et al.
Abstract : Background: Enthesitis in Spondylarthropathy (SpA) is underestimated and often misdiagnosed. A recent paper suggests that tenderness at entheseal sites by itself is not useful in distinguishing between psoriatic arthritis (PsA) and fibromyalgia (FM) 1 Objectives: To evaluate the prevalence of clinical and ultrasonographic (US) signs of enthesitis in PsA patients compared to patients with psoriasis (Ps) without clinical signs of PsA or FM patients. Methods: Study group: 243 consecutive patients (age >18 and ≤65 years), 140 with a diagnosis of PsA (CASPAR criteria), 51 with Ps, and 51 with FM were involved. Rheumatologic assessment: Leeds Enthesitis Index (LEI) and Maastricht Ankylosing Spondylitis Enthesitis Score (MASES). US B mode (Gray scale) and PDUS (Power Doppler) mode assessments were performed bilaterally on common extensor tendon insertion on the lateral epicondyle of the humerus, quadriceps tendon, patellar tendon, medial collateral ligament, and Achilles tendon and plantar fascia insertions on the calcaneus. In US B mode assessment the following abnormalities were recorded: entheseal thickening, entheseal hypoechogenicity, peritendon hypoechogenicity, bony erosions, enthesophytes, and bursae. Vascularisation by PDUS was evaluated at the following areas: cortical bone insertion, body of the tendon, bursa, junction between tendon and enthesis (pre-insertional area). Vascularization was quantified according to the number of vessels (0 =none; 1 =1-3; 2 =4-5; 3 ≥5). Results: Mean age was 48.6±10.7 years. In PsA 50% of patients were females, in psoriasis 54.9%, in FM 92.2%. Height, weight and body mass index (BMI) were significantly lower in FM than in PsA. Clinical evidence of enthesopathy was present in 66.4% of PsA, 58.8% of Ps and 92.2% of FM patients. Clinical evidence of enthesopathy in all the evaluated entheses was present in 23.1% of PsA, 18.1% of Ps and 45.6% of FM patients. Entheseal abnormalities by US were present in 92.1% of PsA, 92.2% of Ps and 74.5% of FM patients. US abnormalities in all the evaluated entheses were present in 53.7% of PsA, 41.2% of Ps and 27.4% of FM patients. Enthesis vascularisation at PDUS in at least one area was observed in 59.3% of PsA, 47.16% of Ps and 35.3% of FM patients. Enthesis vascularisation in all the evaluated areas was present in 19.2% of PsA, 12.7% of Ps and 7.8% of FM patients. Conclusions: Clinical evidence may overestimate active enthesitis in PsA, Ps, and FM. US and PDUS were more frequently positive in patients with PsA and Ps than in those with FM. Therefore, these examinations can be useful in differentiating pain due to enthesitis from the entheseal pain due to FM. References: Marchesoni J Rheumatol 2012; 39 (4), 849-855. Acknowledgements: The ULISSE study was sponsored by AbbVie.The design and study conduct support for this study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the publication. Disclosure of Interest: C. Salvarani Grant/research support: AbbVie, Consultant for: AbbVie, W. Grassi Grant/research support: AbbVie, Consultant for: AbbVie, A. Spadaro Grant/research support: AbbVie, Consultant for: AbbVie, R. D. Grembiale Grant/research support: AbbVie, M. Govoni Grant/research support: AbbVie, Consultant for: AbbVie, R. Ramonda Grant/research support: AbbVie, Consultant for: AbbVie, A. Marchesoni Grant/research support: AbbVie, Consultant for: AbbVie, R. Scarpa Grant/research support: AbbVie, Consultant for: AbbVie, S. De Vita Grant/research support: AbbVie, V. Saragaglia Employee of: AbbVie, R. Merolla Employee of: AbbVie, U. di Luzio Paparatti Employee of: AbbVie, I. Olivieri Consultant for: AbbVie DOI: 10.1136/annrheumdis-2014-eular.2657